Characterizing Satellite Path Through Kelvin‐Helmholtz Instability Using a Mixing Parameter. Issue 2 (27th January 2022) - Settino, A.; Khotyaintsev, Yu V.; Graham, D. B.; Perrone, D.; Valentini, F.
Abstract: We introduce the mixing parameter to analyze the in situ measurements of a Kelvin‐Helmholtz event observed by the Magnetospheric Multiscale mission. We define the mixing parameter, for both ions and electrons, using the well distinct particle energies which characterize the magnetosphere and magnetosheath plasmas. This parameter nicely identifies the different populations which are interacting at the Earth's magnetopause and the boundaries of Kelvin‐Helmholtz vortices. Thus, we analyze the crossing of each structure into a parameter space defined as the space of the electron mixing versus the ion mixing, where specific shapes occur according to the evolutionary phase of the Kelvin‐Helmholtz instability. All along the event, we observe three different types of shapes, namely a straight line, a simple loop, and a complex loop, which likely corresponds to linear waves, steepened waves, and rolled‐up vortices, respectively. The most complex shape (rolled‐up vortex) is observed mostly at the end of the interval, owing to fast growth of the instability which is connected to variations of the solar wind magnetic field orientation. Plain Language Summary: The Kelvin‐Helmholtz instability is a ubiquitous phenomenon in space plasmas, which can develop at velocity shears, such as the ones observed at the interaction regions between the fast and slow solar wind and at the Earth's magnetopause. In the latter case, plasmas with different properties, namely the low density magnetospheric and high‐density magnetosheath plasmas, interact and mix. The evolutionary development of the instability is mainly characterized by three phases, which correspond to a different degree of mixing of both ions and electrons in the magnetosheath and magnetosphere. When the threshold condition is satisfied (which typically corresponds to a super Alfvénic velocity jump) the instability grows linearly and surface waves are generated. At later times, the pressure gradient comes into play, leading to the mixing of the two layers and the generation of vortices. As the instability develops, the mixing degree of the particles of each layer increases and more and more rolled‐up vortices are observed. In this work, we use the mixing degree of ions and electrons to establish which phase the instability is undergoing and to identify the boundaries of the structures. Key Points: We introduce the mixing parameter for in situ measurements of Kelvin‐Helmholtz instability We use the mixing parameter to identify the evolutionary phase of the Kelvin‐Helmholtz instability and the magnetospheric multiscale crossings of vortices We observed more rolled‐up vortices at a late time of the instability due to changes in the solar wind conditions